Study the impact of social networking sites (Facebook) on the academic , psychological and physical achievement of upper secondary stage students in Aqaba - Zaitoun, Isra Shaker (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the effects of social networking sites on students psychologically and physically, as well as on their academic achievement. The researcher has adopted the relational descriptive approach. To achieve the objectives of the study, the researcher prepared a questionnaire and indicate the validity and reliability for it. The study population consisted of (602) male and female students from the upper basic stage (seventh to tenth) in the Alashrah secondary school and Ayla school in Aqaba, and the study sample was selected randomly contained (188) male and female students, of whom (95) were males and (93) Females. The results of the study showed that there is a statistically significant inverse relationship between the level of achievement and the use of social media sites, and the results also showed that there is a direct relationship between students' feeling of fatigue and fatigue and the number of hours they use communication sites. The results also showed that the student is affected psychologically in a positive way and the number of hours spent on using websites Social communication, and the results indicated that there is a statistically significant inverse relationship between parents' knowledge of the password and exposure to social problems. The study concluded with several recommendations, including: The need to study the impact of communication sites on other age groups, and the study also recommended the need to educate parents about how to communicate with their children.
Keywords: students; Academic Achievement; communication website; Upper primary stage; Facebook; Aqaba